“Wairon and Waimansusu”: war boat and trade boat of the Biak people in Papua Indonesia - Albert Rumbekwan; Singgih Tri Sulistiyono; Yety Rochwulaningsih; Endang Susilowati; Ismail Ali; Noor Naelil Masruroh (EDP Sciences, 2025)
This article discusses the traditional boat technology of the Wairon and Waimansusu, which were the main means of transport for the Biak tribe in shipping and trade on the north coast of Papua during the 8th to 19th centuries. Although Papua has various types of traditional boats with their own uniqueness, only a few are able to sail as far as the Maluku Islands. For the Biak Tribe, the Wairon and Waimansusu boats are not only functional, but also have artistic and symbolic value in the maritime history of the eastern region of the archipelago. Using a historical and ethnographic approach, this article reconstructs the manufacturing technology, cruising ability and carrying capacity of both types of boats in the context of voyaging, trading and hunting. Today, the manufacture of Wairon and Waimansusu is increasingly rare, despite their high cultural value and great potential to support the development of marine tourism in Cenderawasih Bay, Papua-Indonesia.